Lactobacillus plantarum fermented Laminaria japonica alleviates UVB-induced epidermal photoinflammation via the Keap-1/Nrf2 pathway - Zixin Song; Qianru Sun; Yuhua Xu; Yuncai Tian; Jiaxuan Fang; Ziwen Wang; Jiman Geng; Dongdong Wang; Changtao Wang; Meng Li (Journal of Functional Foods, 2023)
UVB-induced human immortal keratinocyte (HaCaT) cell damage model was established to investigate the mitigating effect of Laminaria japonica Lactobacillus plantarum subsp. plantarum fermentation broth (LJf) on epidermal photoinflammation and barrier function impairment. Compared to unfermented Laminaria japonica (LJ), LJf contains higher levels of potent substances, as well as stronger in vitro antioxidant activity. LJf is able to scavenge excessive reactive oxygen species (ROS) and increase intracellular antioxidant enzyme content and synthesis levels. We also find that LJf is superior to LJ in inhibiting the release of ILs, TNF-α and MMP-9. LJf also increased the synthesis level of barrier function proteins and decreased the secretion level of Kallikrein-7 (KLK-7), effectively alleviating the level of inflammation, abnormal cell shedding, and impaired barrier function in the epidermis. LJf can inhibit the transcription levels of downstream regulators and inflammatory factors by activating the Nrf2 signaling pathway. Safety experiments reveal that LJf is non-irritating.